Socioeconomic deprivation is a predictor of poor postoperative cardiovascular outcomes in patients undergoing coronary artery bypass grafting. Issue 9 (15th August 2003) - Taylor, F C; Ascione, R; Rees, K; Narayan, P; Angelini, G D
Abstract : Objective: To investigate the effects of socioeconomic deprivation on cardiovascular risk factors and postoperative clinical outcomes of patients undergoing coronary artery bypass grafting (CABG). Design: Retrospective analysis of prospectively collected data. Setting: Surgical population of the southwest of England, April 1996 and August 2000. Study group: Data on 3578 consecutive patients undergoing CABG at the Bristol Royal Infirmary NHS Trust were abstracted. Data were retrieved from the Patient Analysis & Tracking System. Carstairs index was used to measure socioeconomic deprivation of area of residence and was divided into five quintiles, where quintile 1 denotes least deprived and 5 most deprived. Outcome measures: End points were postoperative complications and 30 day mortality. Results: Higher deprivation scores were associated with younger age (p < 0.004), greater body mass index, diabetes, smoking at time of surgery, and higher EuroSCOREs (all p ⩽ 0.001). After adjustment for EuroSCORE, socioeconomic deprivation was independently associated with postoperative myocardial infarction (p = 0.05) and combined postoperative myocardial infarction, stroke, and death (p = 0.016). Hospital length of stay for the patients in the highest quintiles was also significantly longer than for those in the lower quintiles (p = 0.04). Conclusion: Patients undergoing CABG living in areas with high deprivation scores are younger, have more clinical risk factors, and experience more postoperative cardiovascular complications than patients living in low deprivation score areas.